The Influence of Career Development and Organizational Culture on Employee Engagement in Manufacturing Companies in the MM2100 Region - Icha Diahayu Wardani; Muhammad Sapruwan (DEAL: International Journal of Economics and Business, 2024)
This study examines the influence of career development and organizational culture on employee engagement in manufacturing companies in the MM2100 area. Employee engagement, which reflects an employee's emotional and professional connection to the work and organization, is crucial in ensuring operational productivity and efficiency. Challenges such as monotonous tasks and high turnover rates often hinder engagement in a manufacturing environment. This study uses a quantitative approach, and is analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of the study show that career development programs, including skill enhancement and a clear career path, significantly increase employee motivation and commitment. Similarly, an organizational culture that supports collaboration and inclusivity drives an increase in overall engagement. This research highlights the important role of career development and organizational culture in shaping employee engagement. The study suggests that organizations can increase employee productivity and loyalty by investing in structured development programs and creating a positive work environment. These findings provide practical recommendations for human resources practitioners to strengthen employee engagement and optimize organizational outcomes.